Reduced graphene oxide improves the performance of a methanogenic biocathode. (1st August 2022) - Carrillo-Peña, D.; Mateos, R.; Morán, A.; Escapa, A.
Graphical abstract: Graphene-based biocathodes enhance the kinetics of electrochemical conversion of CO2 into bio-methane in comparison to conventional biocathodes. It also promotes biomass development. Highlights: Graphene oxide electrode modifications improve the methanogenic processes in MES systems. Methanobacterium genus is a dominant hydrogenotrophic methanogenic Archaea found in biocathodes. Methane can be produced by means of CO2 at concentrations above 95%. Abstract: Microbial electrosynthesis (MES), a sub-branch of bioelectrochemical processes, takes advantage of a certain type of electroactive microorganism to produce added value products (such as methane) from carbon dioxide (CO2 ). The aim of this study is to quantify the benefits of using a carbon felt electrode modified with reduced graphene-oxide (rgoCF) as a methanogenic biocathode. The current density generated by the rgoCF was almost 30% higher than in the control carbon felt electrode (CF). In addition, charge transfer and ohmic resistances were, on average, 50% lower in the rgoCF electrode. These improvements were accompanied by a larger presence of bacteria (31% larger) and archaea (18% larger) in the rgoCF electrode. The microbial communities were dominated by hydrogenotrophic methanogenic archaea ( Methanobacterium ) and, to a lesser extent, by a low-diversity group of bacteria in both biocathodes. Finally, it was estimated that for a CO2 feeding rate in the range 15–30 g CO2 per m 2 of electrode per day, it is possible to produce a high-quality biogas (>95% methane concentration).